Implementation of school rules to improve the teachers and student discipline - Wanda, Wanda; Ahmad, Syarwani; Fitriani, Yessi (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
This research is motivated by the existence of disciplinary violations committed by teachers and students at SMA Negeri 16 OKU. This happens because there are still obstacles that hinder the process of implementing the value of discipline in increasing teacher and student compliance with the rules of law in SMA Negeri 16 OKU. This study aims to determine the implementation of school discipline in improving the discipline of teachers and students in SMA Negeri 16 OKU. This research uses descriptive methods and qualitative approaches. Data collection techniques in this study include: interviews, observation and documentation. Research Results Broadly speaking, the existing regulations are able to make teachers and students at SMA Negeri 16 OKU become more disciplined. For example, for students who are late, SMA Negeri 16 OKU requires students to ask for a permit from the picket teacher. Many high school students (SMA) are not disciplined. This is a consequence of adolescence, where students violate applicable norms, such as: rampant student brawls, truant students, criminal acts, and drug and drug abuse. However, if this educational institution is properly managed and organized in such a way, especially in consistently applying school rules to students, it will create an educational situation or climate that is conducive to disciplined personal development of students.